PELAKSANAAN FUNGSI PT. JASA RAHARJA DALAM SOSIALISASI PROGRAM KEPADA MASYARAKAT KOTA PEKANBARU TAHUN 2020 - Septia, Drifa Dwita; ', Adlin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
PT Jasa Raharja is a State-Owned Enterprise (BUMN) that implements government programs, namely compensation programs for victims of road traffic accidents. Socialization of PT. Jasa Raharja Pekanbaru Branch is information about the program of providing assistance or compensation provided by PT. Jasa Raharja Pekanbaru City branch to the people of Pekanbaru City who are experiencing road traffic accidents. The problem in this study is the lack of information in the form of how or process so that the people of Pekanbaru City can receive program assistance provided by PT. Jasa Raharja Pekanbaru City Branch thus causing a lack of understanding of the people of Pekanbaru City about the program from PT. The Raharja Service. The purpose of this study is to describe how the implementation of the functions of PT. Jasa Raharja in disseminating the program to the people of Pekanbaru City and describing what factors are inhibiting it. The type of research in this study is using qualitative research with a descriptive approach and the data needed both primary and secondary data obtained through observation, interviews and documentation are then analyzed based on the research problem. The location of the research was conducted at PT. Jasa Raharja Pekanbaru City Branch, using data collection techniques through interviews and documentation. The results showed that the socialization of the program of providing compensation to victims of road traffic accidents by PT. Jasa Raharja Pekanbaru branch in 2020 is considered unsuccessful because it can be seen that there are still many people in Pekanbaru City who do not know about PT. Jasa Raharja and also the program of providing compensation to victims of road traffic accidents in Pekanbaru City. The ignorance of the people of Pekanbaru City is due to the lack of maximum and comprehensive socialization of the compensation program for victims of road traffic accidents provided by PT. Raharja Services. Keywords: Government Program Socialization, Compensation Program